2021
DOI: 10.5194/ems2021-46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of statistical downscaling methods for climate change projections over Spain: present conditions with perfect predictors.

Abstract: <p>The Spanish Meteorological Agency (AEMET) is responsible for the elaboration of downscaled climate projections over Spain to feed the Second National Plan of Adaptation to Climate Change (PNACC-2). The main objective of this work is to establish a comparison among five statistical downscaling methods developed at AEMET: 1) Analog, 2) Regression, 3) Artificial Neural Networks, 4) Support Vector Machines and 5) Kernel Ridge Regression. All the five methods have been applied with a Perfect Prog a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This lack of transferability has been found to be very remarkable in the cases of SVM and KRR. Experiments 1 and 2 (Hernanz et al ., 2021, 2021b) showed how these two methods, which are able to reproduce complex nonlinear relationships and are based on different types of Support Vector Machines, could achieve fairly good results under present conditions, overcoming the linear method REG both with perfect and imperfect predictors, but this study has revealed some important transferability issues in them. This relates with the well‐known problem of machine learning algorithms to deal with new situations to which they have not been trained, and calls in question their suitability for downscaling climate projections, as pointed out by Hsieh (2009).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This lack of transferability has been found to be very remarkable in the cases of SVM and KRR. Experiments 1 and 2 (Hernanz et al ., 2021, 2021b) showed how these two methods, which are able to reproduce complex nonlinear relationships and are based on different types of Support Vector Machines, could achieve fairly good results under present conditions, overcoming the linear method REG both with perfect and imperfect predictors, but this study has revealed some important transferability issues in them. This relates with the well‐known problem of machine learning algorithms to deal with new situations to which they have not been trained, and calls in question their suitability for downscaling climate projections, as pointed out by Hsieh (2009).…”
Section: Discussionmentioning
confidence: 87%
“…The five ESD methods and their different configurations (see Table 5) are briefly presented here. For a more detailed description see Hernanz et al ., 2021. (a) Analog (ANA) methods (Lorenz, 1969; Zorita and von Storch, 1999) are based on the assumption of similar local conditions under similar synoptic situations, and one of their major drawbacks is their limitation to predict values outside of the observed range (Imbert and Benestad, 2005).…”
Section: Downscaling Methods and Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonlinear methods do not add much value here because of the high linear correlation among predictor and predictand (Figure 1). Nevertheless, these very same methods have proved to overcome MLR when using a greater set of predictors (Hernanz et al, 2021).…”
Section: Resultsmentioning
confidence: 99%